Latest Lessons from the Bankruptcy of State-Owned Enterprises (SOEs) in China: An Interpretative Structural Model (ISM) Approach - Qin Lin; Lin Feng; Chatchai Khiewngamdee; Pingping Li; Xiaofei Ye (Discrete Dynamics in Nature and Society)
State-owned enterprises (SOEs) play an important role in China. During the transformation from a planned to a market economy, plenty of Chinese SOEs fell into trouble. Dalian machine tool group (DMTG) who was once a leading enterprise in the Chinese machine tool industry bankrupted in 2017. To explore the causes of its collapse, we employ the interpretative structural model (ISM) to investigate the reasons for its failures from multi-aspect and at different levels. The results indicate that the root cause of this bankruptcy is the top manager’s mismanagement; the lack of a reasonable strategic positioning and long-term product planning are also important factors of DMTG’s failure, and the problems of human resource management accelerated the bankruptcy. Findings provide lessons to be learned from the bankruptcy for SOEs and offer managerial insight into SOEs.